Analisis Faktor – faktor yang Memengaruhi Financial Management Behavior pada Mahasiswa Universitas Muhammadiyah Sukabumi - Vini Eka Paksi; Nor Norisanti; R. Deni Muhammad Danial (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study was to determine the factors that influence financial management behavior. This study uses a quantitative approach by collecting data through questionnaires distributed to 97 respondents. The population in this study were students of the Muhammadiyah University of Sukabumi. The data analysis technique used statistical and descriptive analysis with the help of SPSS Statistic Program Version 20. The results of this study indicate that partially financial attitude shows a significance value of 0.030 or <0.05, then financial self-efficacy shows a significance value of 0.000 or <0.05, it can be concluded that financial attitude and financial self-efficacy have a positive and significant influence on financial management behavior of students. As for locus of control shows a significance value of 0.446 or> 0.05, it can be concluded that locus of control does not have a significant influence on financial management behavior. Furthermore, simultaneously the results show a value of 0.000, it can be concluded that the three independent variables have a significant and positive influence on the financial management behavior of students of the Muhammadiyah University of Sukabumi.